(untitled) (Research, Society and Development, 2022)
The use of fiberglass intraradicular retainers is indicated for the rehabilitation of anterior deciduous teeth severely destroyed, either by caries or trauma, provided that their root portion is intact. This integrative literature review aims to characterize the use of fiberglass pins in anterior deciduous teeth with extensive crown destruction, citing the main conditions that lead to the destruction of these teeth and identifying how they contribute to the aesthetic and functional rehabilitation of children. For its elaboration, based on the PRISMA-ScR strategy and after qualitative analysis, 6 articles were selected in the Pubmed and BVS databases. With this, it was concluded that the use of fiberglass pins has several advantages, as they are able to provide support and retention for future restoration, dissipate masticatory forces, have good adhesion to cementing systems, are technically simple to be made and economically feasible, besides allowing the return of function and aesthetics to patients.